ANALYSIS OF THE INFLUENCE OF DIGITALIZATION ON THE DEVELOPMENT OF HALAL UMKM - R, Hediansyah; S, Suryansyah; S, Fauziah; Risnawati, Risnawati (PERSPEKTIF: Journal of Social and Library Science, 2024)
Digitalization has benefits for business actors, one of which is MSME players. Digitalization has advantages such as making it easier to attract consumers through digital or online marketing, reducing costs, and expanding marketing networks. Digital marketing basically has quite a positive influence, but the use of digital marketing is still very low due to the readiness factor, which is still an obstacle for MSME players in Indonesia. Therefore, this research was made with the aim of analyzing the effect of digital marketing on halal MSMEs around the Gunadarma University campus using the digitalization marketing variable approach (X1) and literacy variable (X2) on the development of halal MSMEs (Y). The method in this study is descriptive-qualitative and uses primary data obtained through structured interviews with halal MSMEs, especially those around the Gunadarma University campus in Kelapa Dua, Depok City. The sample used in this study was 10 respondents from halal MSME actors around the Gunadarma Depok campus.